Sudut Pandang Al-Ghozali Dalam Memaknai Spiritualitas Shalat - Fatakhul Huda (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
One of the obligations of Muslims is prayer. Prayer is an obligation that requires the participation of two organs, namely the body and the heart. Even though he has prayed five times, his prayer cannot be said to be perfect if it is not accompanied by